Depolitisation and professionalisation of administration in Republic of Serbia - Lončar, Zoran (Zbornik radova Pravnog fakulteta u Novom Sadu, 2014)
Depolitisation and professionalisation of the administration are some of the basic principles of administrative reform, which are implementing since 2004., in order to achieve the most important European standards in the Republic of Serbia.  However, the new legislative framework in the field of civil service system is not fully completed, because it has to be finished the reform of the provincial and local civil service system, but there also appeared certain deviations from the depolitisation and professionalisation, as prescribed standards on the state level, which significantly depart a reform of public administration from desired and set goal. Frequent changes of government are one of the most important reasons which influenced that despite strict legal solutions, in practice, the process of depolitisation and professionalisation of public administration has ignored, what is reason why almost half of the civil servants on the position are not selected on the basis of the contest, according the legal requirements. Considering the fact that the selection of senior civil servants on the basis of competition, at this moment, is more exception than rule, in order to achieve depolitisation and professionalisation of public administration, it would be necessary immediate termination of function for all civil servants who are appointed without competition, as the current Law on Civil Servants stipulates, as well as the observance of prescribed requirements and bidding procedures for the selection of future civil servants.   In order to achieve further professionalisation of the administration, it  should be continue improvement of the civil service system, particularly with further development of the career system, where priority should be given to continuously professional development of civil servants, as well as improving the system of promoting and rewarding, through the reform of the wage system.  At the provincial and local level, with new law of provincial and local servants, based on contemporary standards, should be regulated the issues of their legal status, and finally give opportunity to provincial and local authorities to carry out much-needed process of depolitisation and professionalisation of provincial and local servants. After elimination  of observed deficiencies in the civil service system, the Republic of Serbia will be able to say that is fulfilled one of the main European standards in the field of administrative reform.
Keywords: civil service system; professionalisation of the administration; depolitisation of the administration; public administration; administration